THE INFLUENCE OF MULTIMEDIA ON TEACHING SPEAKING TO INTROVERT STUDENTS - Bernadetta Eko Putranti; Suprih Ambawani; Siti Saudah (BULLET : Jurnal Multidisiplin Ilmu, 2025)
The purpose of this study was to determine the effect of multimedia on introvert students in developing their speaking skills. This study used experimental research and ex-post facto data to determine the differences in students' speaking abilities before and after treatment. Pretest and Posttest of the study were conducted to analyze the effect of multimedia on speaking activities. Respondents were first-semester students majoring in Geological Engineering and Environmental Engineering at the AKPRIND Yogyakarta Institute of Science & Technology (now: AKPRIND Indonesia University) in the 2023/2024 academic year. The results of the data analysis showed that the Shapiro-Wilk normality test was conducted to assess the distribution of difference scores, resulting in a p-value of 0.0001458 (p <0.05), which indicates that the data were not normally distributed. Based on the results of the p-value, the non-parametric Wilcoxon Signed-Rank Test was used instead of the paired t-test to determine whether there was a statistically significant difference between the two sets of scores. Results of non-parametric analysis in R: Wilcoxon signed-rank test with data continuity correction: dmb$POST and dmb$PRE V = 1016, p-value = 1.16e-08*** Alternative hypothesis: the actual location shift is not equal to 0 The Wilcoxon test results (p = 1.16e-08, or 0.0000000116) show a statistically significant difference between the pre- and post-test scores. This indicates a significant improvement in students' speaking ability, after the multimedia presence intervention.